Identification of Essential Proteins as Promising Therapeutic Targets against Drug Resistant Strain of Staphylococcus aureus: An in silico Approach - Das, Monish Mukul; Chakraborty, Sayan; Mondal, Avijit; Guha, Tapas (International Journal of Pharmaceutical Investigation, 2025)
Background Staphylococcus aureus is a gram-positive pathogen which contributes community-associated and nosocomial serious diseases and it has become resistant to various antimicrobials. Owing to rapid advent and continuous dispersal of MRSA strains, there is an urgent need to identify therapeutic targets to deal with global threat of persistent infections caused by MRSA strains. Materials and Methods Machine learning approach (DNN), subtractive genomics channel analysis, qualitative characterization for cellular location of proteins, structure-based modelling and eventually, analysis for stereochemical quality and physico-chemical properties of target protein (WP_000249839.1) were employed to identify potential drug target. Results 105 non-homologous essential proteins identified as common drug targets, were analysed using BLASTp against ‘VFDB’ which resulted in 25 virulent proteins. Among them, 2 were identified as antibiotic-resistant proteins. One out of 2 antibiotic resistant proteins, was identified as cytoplasmic protein (DapD) which was selected as drug target. The stereochemical quality and physico chemical analysis confirmed ‘DapD’ protein as potential drug target. Conclusion Unique strategy employed in this study would be useful in future in comprehending pathogenesis of bacterium as well as developing and designing potent therapeutic candidates.
Keywords: MRSA; DNN; VFDB; DapD; MSSA; DEG; WGS; GA; SVM; ARG-ANNOT